DESCRIPTION OF A DE CHARGE WITNESS DECISION OF THE JUDGE IN CRIMINAL FINANCING - Madinah Adama; Hambali Thalib; Hamza Baharuddin (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal